Determinants of repeated induced abortion among reproductive age group women visiting health facilities of Sidama regional state, Ethiopia, 2020: Facility based unmatched case-control study - Mekonen Binayew; Daniel Sisay W/Tsadik; Tizalegn Tesfaye; Habtamu Endashaw Hareru; Helen Ali Ewune; Getachew Assefa; Selamawit Semagn Kebede; Tinsae Shemelise Tesfaye; Addisu Alemayehu Gube (Elsevier, 2022)
Background: Induced abortion is the intentional termination of pregnancy before the 28th weeks of gestation. Despite the urgency of the situation, little is known about the factors that lead to induced abortion. Therefore, the aim of this study was to identify determinants of repeated induced abortion among reproductive age group women at health facilities of Sidama region, Ethiopia. Methods: Unmatched case-control study had been done. A total of 116 cases and 234 controls were included in the study. Cases were women with two or more induced abortions and controls with one induced abortion. Data was entered to Epi data version 3.1 and exported to SPSS 20 for analysis. Bivariate and multivariate logistic regression analysis with 95% confidence interval was done. Result: A total of 116 cases and 234 controls completed the interview with response rate of 95% and 94.9% for cases and controls. Urban resident (AOR, 95% CI = 4.9 [2.1-11.3]), primary education (AOR, 95% CI = 0.21 [0.06-0.8]), multiple sexual partner (AOR,95% CI = 2 [1.1-3.7]), fertility awareness (AOR,95% CI = 6.8 [2.5-18.2]) ,age at first sex (AOR,95% CI = 4 [1.9-8.7]) and not perceived abortion as painful procedure (AOR, 95% CI = 2.5 [1.2-5.3]) were significant factors of induced abortion. Conclusion: Residence, education, number of sexual partner, age at first sex, fertility awareness and perception of abortion pain were determinant factors. Education, health information, family free discussion & reproductive health service utilization should be promoted.